Effectiveness of Nutrition Program for Toddlers Through Supplementary Food Provision (PMT) at Posyandu, Ranoteta Village, Watubangga District, Kolaka Regency - Widi Laksamana; Maulid; Fetni (Jurnal Dialektika: Jurnal Ilmu Sosial, 2026)
The fundamental problem of this research background is the low participation and concern of parents towards nutritious food, as well as suboptimal service from the Community Health Center (Puskesmas) which often arrives late, thus reducing public trust and enthusiasm. The purpose of this study is to analyze the effectiveness of the PMT program in improving the nutritional status of toddlers and to identify supporting and inhibiting factors in its implementation. This study uses a qualitative approach with a case study method to explore the phenomenon studied in depth. This research model is focused on descriptive analysis to provide a systematic overview of the facts found. Primary data was obtained through data collection techniques in the form of interviews, direct field observations to see the real conditions at the research location, and relevant documentation studies. The collected data were then analyzed using qualitative data analysis methods which include data reduction stages, narrative data presentation, and drawing conclusions. The results of this study indicate that the PMT program at the Posyandu Ranoteta Village has not been running effectively. Based on the effectiveness of the program consists of five indicators, namely: program success, target success, satisfaction with the program, input and output levels, achievement of overall objectives. The five indicators have not been effective due to limited implementation, with activities occurring only once a month, a lack of variety in the PMT menu, and a lack of community participation in integrated health post (Posyandu) program activities. This is compounded by a lack of parental awareness of the importance of a nutritious PMT menu for improving toddler nutrition.Keywords: Program Effectiveness, PMT, Toddler Nutritional Status, Posyandu, Community Participation.